Stone fruits: Sweet cherries (Prunus avium L.) - Toivonen, Peter M.A.; Manganaris, George A. (My University, 2020)
Sweet cherries are a high value, short storage life fruit. Value in the market place is dependent on quality parameters including firmness, soluble solids content, red fruit color, stem green color and freedom from defects (pitting, pebbling, decay). Quality at the market place can be assured if proper at harvest temperature management and good controlled or modified atmosphere technologies are applied. This chapter provides brief guidance on the potential issues that must be faced and overcome to achieve good market quality of cherries that are shipped both short and long distances.
Keywords: Stone fruits; Sweet cherries